Illuminated Caxtons and the Trade in Printed Books. (8th September 2021) - James‐Maddocks, Holly
Abstract: This article suggests that the illuminated initials and borderwork added to ten early printed books in England are attributable to a single illuminator, the 'Incunables Limner', an individual for whom there is circumstantial evidence that he specialized in the illumination of printed books. Five of these books are copies of William Caxton's Golden Legend (Westminster, 1483–84), while the other five are Continental imprints (two from Strasbourg, and one from each of Basel, Verona, and Parma) printed between 1476 and 1484. In addition, a second illuminator can be identified in a sixth copy of Caxton's Golden Legend, working to the same design as that employed within the five copies decorated by the Incunables Limner. The possibility is considered that books illuminated by the Incunables Limner were products of Caxton's overseas trade, and that it was through acting in this capacity that the artist's specialization was viable. The Continental books are explored for what they might imply about Caxton's wider book-selling strategies, and three with evidence for early English ownership are selected for particular attention.